(untitled) (Scientific journal of the Fergana State University, 2026)
In the Zominsuv Reservoir area, recognized as one of the earliest centers of tourism development in Uzbekistan, the impact of natural and geographical factors on tourism development has been deeply studied and systematically analyzed on a scientific basis. The region’s mountainous relief, climatic conditions, water resources, forests, and flora and fauna are important factors in shaping tourism potential, providing a scientific foundation for the development of tourist routes, recreation areas, and eco-tourism projects.